Characterisation of the locally sourced agricultural wastes as biosorbents - Noor Safitri, Bte P.Sarman (Universiti Malaysia Sarawak (UNIMAS), 2012)
Biosorption is an economically feasible technology; it has many attractive features including removal of metals over a broad range of pH and temperature, rapid kinetics of adsorption and desorption, low capital and operation cost. Agriculture wastes are potential biosorbents. They can be obtained easily and this allows significant cost savings in comparison to other technologies. In this study, we characterized the physicochemical, functional and morphological properties of various locally sourced agricultural wastes i.e., banana trunk, coconut husk, rice husk, sago wastes and oil palm empty fruit bunch. The analyses include moisture, ash, pH, conductivity, iodine number, Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR). The agricultural wastes were characterised by a pH between 3 and 6.8 with sago hampas and banana trunk exhibited a lower pH. In term of ash content, rice husk showed higher amount. The FTIR spectra of agricultural wastes were characterised by the presence of lignocellulosic components. PCA demonstrated that different wastes are distinguishable. Morphologically, better developed pores were observed on coconut husk, banana trunk and sago hampas compared to rice husk and fruit bunch. Nevertheless, no significant different was concluded in the iodine number of various biomass.